Learning GitHub actions for DevOps CI/CD. (Packt Publishing, 2023)
Workflows are defined by a YAML file checked into your repository and will run when triggered by an event in your repository, or they can be triggered manually, or on a defined schedule. GitHub Actions makes it easy to automate all your software workflows, now with world-class CI/CD. Build, test, and deploy your code right from GitHub. Make code reviews, branch management, and issue triaging work the way you want. In this intensive course, you will learn the fundamentals of GitHub Actions workflow in a compact timeframe. The course covers important concepts such as the workflow structure and components, events, jobs, steps, and runners. It also dives into various topics such as environment variables, GitHub variables, secure password storage, and manual approvals. Additionally, the course teaches techniques for sharing values between steps and jobs and explains the use of self-hosted runners. The course concludes with a demonstration of preparing an infrastructure as code (IAC) template with Bicep and deploying it through a GitHub Action workflow. The course will equip you with the skills to automate your entire software workflow using GitHub Actions, from idea to production. By the end of this course, you will have a solid understanding of how to use GitHub Actions to automate your software workflows. What You Will Learn Understand GitHub Action workflow basics Learn about workflow components (event, job, step, runner) Add a self-hosted runner and execute jobs using it Design an IAC template with Bicep to deploy infrastructures Build, push, and deploy Docker containers Deploy a container to the Azure web app for optimal performance Audience This course is designed for cloud consultants who work on platform automation requirements or those who want to experience the power of Azure Serverless Computing. Azure IAAS and PAAS administrators, application developers, and cloud computing enthusiasts will also gain a lot from this course. To get the most out of this course, you should know about YAML file syntax; some basic understanding of the command line (Win CMD/Unix Shell) will help you quickly grasp the concepts; and Visual Studio Code should be installed on your laptop. About The Autho Vijay Saini: Vijay Saini is an accomplished IT professional who brings a wealth of expertise to the table. With a diversified background across multiple domains, Vijay has proven himself a valuable asset to his current role as a leading cloud service provider. His strong focus on automation has resulted in significant cost savings for the business, making him a valuable asset to the team. Vijay is highly knowledgeable in the areas of Microsoft Azure, cloud technologies, DBMS, and Python, and is a specialist in automation using PowerShell. With a passion for teaching, Vijay has leveraged e-learning platforms to share his expertise with others, helping them develop their own skills and knowledge.